Green Work Engagement: A Literature Review - Marini, Marini; Handoyo, Seger; Sukadiono, Sukadiono (RSF Conference Series: Business, Management and Social Sciences, 2023)
Green Work Engagement represents a concept denoting the extent of employee involvement and active participation in sustainable initiatives within their workplace. In this context, employee engagement encompasses a resolute commitment to advocate for sustainable practices to mitigate detrimental effects on the environment, society, and various societal facets. The primary objectives of Green Work Engagement encompass: (1) identifying influential factors contributing to employee participation in sustainable practices, encompassing intrinsic and extrinsic motivation, organizational dedication, participation in decision-making, and supportive work environment elements; (2) analyzing the degree of employee engagement in sustainable practices and its correlation with organizational performance, including aspects such as productivity, efficiency, and innovation; (3) assessing the ramifications of employee participation in sustainable practices on their satisfaction and well-being, encompassing job satisfaction, talent retention, and burnout rates; and (4) elucidating the implications of Green Work Engagement on environmental continuity, comprising the reduction of adverse environmental impacts, enhancement of sustainability policies, and elevation of the company's reputation concerning sustainability matters. The research methodology employed in this article is a literature review. Notably, Green Work Engagement or engagement focused on environmentally friendly practices, significantly and positively influences employee performance within an eco-conscious context. Given this, it is advised that company management intensify efforts to enhance Green Work Engagement by fostering a greater understanding among employees about the company's commitment to environmental consciousness.